2018
DOI: 10.1080/15384047.2018.1550569
|View full text |Cite
|
Sign up to set email alerts
|

Combined α-programmed death-1 monoclonal antibody blockade and fractionated radiation therapy reduces tumor growth in mouse EL4 lymphoma

Abstract: The programmed death (PD) pathway is frequently present in the tumor microenvironment (TME) and suppresses tumor immunity by inhibiting the activity of tumor-infiltrating lymphocytes (TILs), particularly, CD8 + lymphocytes. PD immunotherapy involves stimulation of the immune response in the region surrounding the tumor but is insufficient to prevent tumor progression. Therefore, in this study, we examined the effects of combined PD immunotherapy with fractionated radiotherapy (RT) on antitumor immunity and tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Reports have shown that a stronger antigen-specific T-cell-mediated immune response typically occurs on the second exposure to the same antigen. , Therefore, to determine the specific killing effect of nanovaccines on tumor cells, we collected splenocytes from immunized mice and used them in a coculture as effector T cells (E) to assess the response of CD8 + T-cell subpopulations of splenocytes to target cells B16F10 (T). , Compared to the blank, the number of splenocytes in the Obsl1, CpG + Obsl1, and 2′F-CpG/Obsl1 nanovaccine groups that showed dosage-dependent CD8 + T-cell activity against target cells significantly increased when the E/T ratios were 10:1, 20:1, and 40:1, as shown in Figure l. Furthermore, the nanovaccine group exhibited higher cytotoxicity than the blank, Obsl1, and CpG + Obsl1 groups.…”
Section: Resultsmentioning
confidence: 99%
“…Reports have shown that a stronger antigen-specific T-cell-mediated immune response typically occurs on the second exposure to the same antigen. , Therefore, to determine the specific killing effect of nanovaccines on tumor cells, we collected splenocytes from immunized mice and used them in a coculture as effector T cells (E) to assess the response of CD8 + T-cell subpopulations of splenocytes to target cells B16F10 (T). , Compared to the blank, the number of splenocytes in the Obsl1, CpG + Obsl1, and 2′F-CpG/Obsl1 nanovaccine groups that showed dosage-dependent CD8 + T-cell activity against target cells significantly increased when the E/T ratios were 10:1, 20:1, and 40:1, as shown in Figure l. Furthermore, the nanovaccine group exhibited higher cytotoxicity than the blank, Obsl1, and CpG + Obsl1 groups.…”
Section: Resultsmentioning
confidence: 99%
“…Several preclinical studies have demonstrated that radiotherapy combined with immunotherapy has three major benefits: (1) radiotherapy can regulate the tumor microenvironment and increase the infiltration of cytotoxic T lymphocytes, thereby enhancing the effect of tumor regression and achieving better local control; (2) produce effector and memory immune cells to maintain antitumor immunity, thereby avoiding tumor recurrence and prolonging local control time; and (3) induce “distant effect” and reduce the risk of distant metastasis [ 27 29 ]. In a phase 2 trial in Korea, 28 patients with stage Ib-III ESCC received chemoradiotherapy along with pembrolizumab, followed by surgery and postoperative pembrolizumab maintenance therapy.…”
Section: Discussionmentioning
confidence: 99%
“…T cell activity through ICI therapy represents an important breakthrough in treating human cancer. ICI treatment alters the TME, the systemic immune microenvironment, and the immune cell composition, thereby resulting in tumor inhibition [10,42]. Unfortunately, only a small fraction of patients treated with ICI are responsive [43,44].…”
Section: Systemic Immune Response To Immune Checkpoint Inhibitorsmentioning
confidence: 99%